Vaccines, A key towards health of travellers - Swayam Pragyan Parida; Vikas Bhatia (Wolters Kluwer Medknow Publications, 2017)
Globally a surge in international travel has been seen. It has led to importation and establishment of disease causing organisms in a previously naive area resulting in onset of epidemics and increase in size of the endemic area. Vaccines are available for some diseases and are considered as one of the best method to prevent diseases. There are vaccines which are routinely recommended for all irrespective of travel and few vaccines e.g., Yellow fever, Meningococcal and OPV are mandatory for travellers as part of International Health Regulation. Vaccination of travellers provides benefit in two ways i.e. protection of individuals and thereby protecting the population of entire country.